2018
DOI: 10.1121/1.5048421
|View full text |Cite
|
Sign up to set email alerts
|

A model and experimental approach to the middle ear transfer function related to hearing in the humpback whale (Megaptera novaeangliae)

Abstract: At present, there are no direct measures of hearing for any baleen whale (Mysticeti). The most viable alternative to approaches to simulate the audiogram is through modeling outer, middle, and inner ear functions based on the anatomy and material properties of each component. This paper describes a finite element model of the middle ear for the humpback whale () to calculate the middle ear transfer function (METF) to determine acoustic energy transmission to the cochlea. The model was developed based on high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…As this study focused on 1- to 4-kHz sonar signals, we might expect humpback whales to have the best hearing in the frequency band of the sonar ( 36 ) and hence be more sensitive to disturbance by those sounds. Instead, the most sensitive species to both stimuli in our study was the northern bottlenose whale.…”
Section: Discussionmentioning
confidence: 99%
“…As this study focused on 1- to 4-kHz sonar signals, we might expect humpback whales to have the best hearing in the frequency band of the sonar ( 36 ) and hence be more sensitive to disturbance by those sounds. Instead, the most sensitive species to both stimuli in our study was the northern bottlenose whale.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new experimental setup was used to visualize the motion of the isolated otoliths in 4D, providing insights into the motion of auditory structures (Maiditsch et al, 2022). Besides, finite element modeling offers an alternative way to study the roles of the otoliths in fish hearing and has been widely used in odontocetes to investigate sound transmission and reception (Cranford and Krysl, 2015; Song et al, 2021; Tubelli et al, 2018), which may facilitate more studies on hearing mechanism in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Note that Chicken' hearing range was extended from infrasound (9.1 Hz) like Elephant and Humpback whale. Carp (Vetter et al, 2018); Bottlenose dolphin (Houser and Finneran, 2006); Humpback whale (Tubelli et al, 2018).…”
Section: Hearing Rangementioning
confidence: 99%
“…2). For example, the bottlenose dolphin (Tursiops truncatus) is able to distinguish sounds from 100 Hz to ultrasounds up to a frequency of 150,000 Hz (Houser and Finneran, 2006) while the humpback whale (Megaptera novaeangliae) and the elephant (Elephas maximus) are able to detect infrasound as low as 15 (Tubelli et al, 2018) and 17 Hz (Heffner and Heffner, 1980), respectively. This capacity to detect infrasound is not restricted to large mammals as it has been shown that chickens (Gallus gallus domesticus) are also able to detect infrasound as low as 9 Hz (Hill et al, 2014).…”
Section: Hearing Rangementioning
confidence: 99%